The Impact of the Digital Yuan on the Transmission Mechanism of Monetary Policy in China - Liang, Xiao (2025)
This thesis examines how the Digital Yuan (e-CNY) affects the transmission of monetary policy in China by combining theoretical, qualitative, and empirical analysis. Its theoretical framework outlines China’s quantity-based and price-based policy tools and evaluates how digital currency features such as traceability and programmability reshape liquidity control and market autonomy. The qualitative analysis highlights both opportunities and risks: the Digital Yuan may weaken the effectiveness of the money multiplier while strengthening the central bank’s guidance of interest rates. The empirical study uses provincial quarterly panel data from 2015 to 2023 and constructs a fixed-effects model incorporating the Monetary Digitalisation Index (MDI). The results indicate that the Digital Yuan enhances price-based transmission mechanisms, has a limited but observable impact on quantity-based mechanisms, and exerts stronger transmission effects in eastern provinces with higher levels of financial development.